Saving seed and food grains - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Wood ash, sand, eucalyptus and guava leaves can be used to protect small quantities of seed and food grams from insect attack. Damage can also be avoided by removing crops from the field as quickly as possible after harvesting. In Senegal, Peace...